Experimental study of potassium release during biomass-pellet combustion and its interaction with inhibitive additives. (15th January 2020) - Liu, Yingzu; Wan, Kaidi; He, Yong; Wang, Zhihua; Xia, Jun; Cen, Kefa
Abstract: In the present study, two types of biomass were investigated as typical agricultural and woody biomass fuel, i.e., corn straw and poplar. Firstly, laser induced breakdown spectroscopy (LIBS) was employed to investigate the release characteristics of potassium (K) from a burning biomass pellet. In order to further investigate the correlation between K release and the combustion process, combustion parameters including pellet surface temperature and pellet diameter were simultaneously measured with LIBS. A dual-peak trend is observed in the K release history of poplar, but only a single peak is found in that of corn straw. Both biomass samples show the strongest K release during the devolatilization stage in comparison with the subsequent char burnout and ash cooking stages. Similar tendencies are observed between K release and pellet temperature, which suggests that K release is closely related to the combustion process. The K release mechanism can be attributed to temperature rise and therefore breakdown of chemical bonds during combustion. Then the release of different chemical forms of K was investigated by chemical fractionation treatment of the biomass samples. The released amount of H2 O-soluble, NH4 Ac-soluble and HCl-soluble potassium compounds were obtained. The H2 O-soluble potassium is found to be the major released potassium compound. Finally, four kinds of additives (two pure additives, i.e., silica and alumina, and two typical natural mineral additives, i.e., kaolin and mica) were added to the biomass samples to investigate their inhibition effects on K release. The natural sorbent additives show better inhibition effects than the pure ones.